Cultivation strategy to improve chemical profile and anti-oxidant activity of Sideritis perfoliata L. subsp. perfoliata - Chrysargyris, Antonios; Kloukina, Charalampia; Vassiliou, Rea; Tomou, Ekaterina Michaela; Skaltsa, Helen; Tzortzakis, Nikos G. (My University, 2019)
Due to the remarkable medicinal properties of Sideritis spp, the commercial demand for the plant is continuously on the rise both in the European and in the global market. Cultivation of Sideritis species have been occurred to successfully meet the need for mass production of high-quality plant material. The present study was undertaken in order to investigate the impact of different cultivation practices (conventional versus organic cultivation; full versus deficit irrigation) in the yield and phytochemical profile of S. perfoliata L. subsp. perfoliata from Cyprus, under two harvestings for biomass production. Deficit irrigation decreased plant growth, but increased dry matter content. The content of chlorophylls and the nitrogen and potassium content decreased in organically grown plants. Both organic cultivation and/or deficit irrigation increased total phenolics, flavonoids, vitamin C and antioxidants. Essential oil yield increased under deficit irrigation at the 2nd harvest, while essential oil composition fluctuated among the treatments. Infusions of each plant material were prepared according to the European Medicines Agency (EMA) monograph. Based on their NMR spectra, the deficit-irrigated plants from conventional cultivation were the most rich in secondary metabolites and chosen for further chemical analysis. Six iridoids such as three flavonoids, two phenylethanoid glucosides and one phenolic acid have been isolated indicating new knowledge on the effects of cultivation practices on plant secondary metabolisms with putative industrial applications and interest.
Keywords: Sideritis perfoliata L. subsp. perfoliata; Organic cultivation; Deficit irrigation; Iridoids; Antioxidant activity; NMR metabolomics strategy